Post-exercise differential response of central and brachial blood pressure in patients with coronary artery disease: A randomized crossover trial - João Luís Marôco; Vitor Angarten; Rita Pinto; Vanessa Santos; Bo Fernhall; Helena Santa-Clara; Xavier Melo (PLoS ONE, 2025)
The post-exercise hypotension response is controversial among patients with coronary artery disease (CAD). Factors behind this disparity may include post-exercise differential effects on central and brachial blood pressure (BP), exercise intensity and inter-individual variability. Thus, we investigate group and individual central and brachial BP responses 5, 15 and 30-min after combined exercise of different intensities in participants with and without CAD. Seventeen participants with stable CAD and eighteen aged-matched controls (52–81 years) completed an acute bout of high and moderate-intensity combined exercise. Brachial and central systolic (cSBP) pressures were assessed via oscillometry and carotid tonometry, respectively. Central pulse wave velocity was also measured. Group mean changes were examined with linear mixed models, and bSBP and cSBP post-exercise individual responsiveness quantified via the region of practical equivalence and highest density interval, a Bayesian decision rule. Regardless of exercise intensity, cSBP was persistently increased during recovery in participants with CAD (difference 30 –baseline (d30-bas) = 10, 95% CI: 4 to 17 mmHg, p = 0.001) but reduced in controls (d30-bas = -13, 95% CI: -19 to -7 mmHg, p = 0.003). bSBP was unchanged in both groups (CAD: d30-bas = 1, 95% CI: -3 to 6 mmHg, p = 0.995, control: d30-bas = -4, 95% CI: -2 to 8 mmHg, p = 0.999). Most participants with CAD exhibited sustained elevations in cSBP (n = 10), while most controls were post-exercise hypertensive responders (n = 11) with changes >|5| mmHg. We found differential post-exercise effects on central and brachial BP independent from combined exercise intensity but not clinical population. Clinical trials.gov registration ID: NCT06617117